Peran Mediasi Locus of Control pada Perilaku Keuangan - Asep Saepuloh; Sukaris sukaris (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2019)
Financial problems for the next five to ten years are spending greater than income, increasing loans, and not being able to have a place to live because income and housing installment costs are not balanced, on the other hand Indonesian people's awareness of the importance of financial literacy is currently low. The purpose of this study was to determine the mediating role of the locus of control between financial knowledge, financial attitudes towards financial management behavior. The sample used was 100 respondents, the analysis technique used was structural equation modeling with WarpPLS. The results show that internal and external locus of control variables are not mediating variables between financial knowledge, financial attitudes towards financial management behavior.